2019
DOI: 10.1007/s00167-018-5317-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute knee dislocations: anatomic repair and ligament bracing as a new treatment option—results of a multicentre study

Abstract: Purpose The literature shows no consensus regarding the best method and timing for the treatment of acute knee dislocations. Studies indicate that a one‐stage procedure performed in the early stages of injury can lead to superior results. The aim of this study was to evaluate the results after performing early surgical repair with additional suture augmentation (ligament bracing) of all torn ligaments in acute knee dislocations. Methods In this prospective multicentre study, 73 patients with an acute type III … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
3
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(120 citation statements)
references
References 49 publications
8
95
3
14
Order By: Relevance
“…When looking at the incidence of neurological injuries in this cohort, Niall et al showed that the majority (41%) occurred in patients with KD-IIIL injuries which is slightly less frequent than found in the present study [43], which may be explained due to our small sample size of patients with KD-IIIL injuries (n = 7). In general, neurovascular injuries are associated with KD-IIIL and KD-IV dislocations, which is consistent with the results found in the present study [46].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When looking at the incidence of neurological injuries in this cohort, Niall et al showed that the majority (41%) occurred in patients with KD-IIIL injuries which is slightly less frequent than found in the present study [43], which may be explained due to our small sample size of patients with KD-IIIL injuries (n = 7). In general, neurovascular injuries are associated with KD-IIIL and KD-IV dislocations, which is consistent with the results found in the present study [46].…”
Section: Discussionsupporting
confidence: 93%
“…When reviewing recent repair studies, Hua et al performed open single-stage repair in all injured ligaments in 17 MLIKs and reported no knee laxity during final follow-up (mean 4.8 years) [20]. Given Heitmann et al supported these results by reporting that 91.3% of cases had clinical stable knees following primary repair with additional suture augmentation of all injured ligaments in 69 MLIKs (KD-III and IV) at a mean follow-up of 14 months [46]. In their study, secondary ACL reconstruction was performed in four patients (seven percent), while two underwent multiligamentous reconstruction (three percent) following instability.…”
Section: Discussionmentioning
confidence: 99%
“…27 Similarly, the mean IKDC score (78.6 points) in this study was within the range of previous reports, from 74.5 to 83.8. 11,27,40 Because of the small number of patients in the irreducible group, the absence of significant differences between the 2 groups could potentially be attributed to a lack of power.…”
Section: Discussionmentioning
confidence: 99%
“…Die Technik des "Bracings" soll hierbei eine frühe Gelenkmobilisierung mit Schutz der in Konsolidierung begriffenen Bandstrukturen ermöglichen [20]. Die Techniken I-III sollten in den ersten 2 Wochen nach der Verletzung erfolgen; in der chronischen Situation steht nahezu ausnahmslos die Ligament-Rekonstruktion zur Verfügung [2] [7].…”
Section: Operative Therapieunclassified